2013
DOI: 10.1253/circj.cj-13-0453
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamism and Cardiac Fate

Abstract: Defects in mitochondrial biogenesis are well known to contribute to cardiac dysfunction. By contrast, mechanistic details of essential homeostatic mechanisms that maintain mitochondrial health in the heart are only recently being uncovered, and the pathological potential of these processes is largely hypothetical. I will review the role of mitochondrial dynamics, focusing on cyclic organelle fission and fusion, in normal and diseased hearts. Special attention is given to recent insights into the non-canonical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 99 publications
0
23
0
Order By: Relevance
“…15 We showed that both agents opened mPTP and depolarized mitochondrial membrane potential (∆Ψm), indicating a functional link between MT reorganization and mPTP in cardiac Mitochondria undergo frequent and dynamic morphological changes, and this is regulated by fission and fusion proteins located in the IMM and OMM. 12 According to recent reports, among these, mitofusin-2 (Mfn2), a fusion protein existing in the OMM, is related to the regulation of mPTP. 13 Because both Mfn2 and the Miro-Milton-KHC complex are located in the OMM, interaction could occur between these proteins.…”
Section: Microtubules and Mptpmentioning
confidence: 99%
See 2 more Smart Citations
“…15 We showed that both agents opened mPTP and depolarized mitochondrial membrane potential (∆Ψm), indicating a functional link between MT reorganization and mPTP in cardiac Mitochondria undergo frequent and dynamic morphological changes, and this is regulated by fission and fusion proteins located in the IMM and OMM. 12 According to recent reports, among these, mitofusin-2 (Mfn2), a fusion protein existing in the OMM, is related to the regulation of mPTP. 13 Because both Mfn2 and the Miro-Milton-KHC complex are located in the OMM, interaction could occur between these proteins.…”
Section: Microtubules and Mptpmentioning
confidence: 99%
“…The mitochondrial fusion is regulated by Mfn2 located on the OMM and optic atrophy 1 (Opa1) located on the IMM. 12 In the neuron system, Mfn2 directly interacts with Miro, and both Mfn2 and Miro are required to cooperatively mediate mitochondrial transport. 21 Miro can regulate mitochondrial morphology, independently from mitochondrial transport in H9c2 cells.…”
Section: Mt Disorganization Induces Mitochondrial Fragmentation In H9mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Mitochondria also generate ROS as natural byproducts of oxygen metabolism in the electron transport chain. Under normal conditions, most of the electrochemical proton gradient is used to generate ATP through ATP synthase, and only 0.1% of the total oxygen consumption leaks from the respiratory chain to generate ROS.…”
Section: Mitochondrial Ros Production In Dmmentioning
confidence: 99%
“…Morphology is regulated by mitochondrial fusion (MFN1, MFN2, OPA1) and fission (DRP1, FIS1) proteins. 5,6 Mitochondrial fission has been shown to precede mitophagy, and mitochondrial elongation during starvation prevents mitochondrial destruction by mitophagy (Figure 1). 4,7 BCL-2 and BCL-XL are anti-apoptotic proteins that bind BECLIN-1 to prevent its activation, and disruption of this interaction is essential for initiation of autophagy.…”
Section: Multiple Pathways Regulate Myocardial Mitophagymentioning
confidence: 99%